Bamboo-Based Soil Carbon Sequestration: A Sustainable Pathway for Soil Health and Climate Mitigation - Mugunthan, Perumal; Mohd Effendi, Wasli; Hafsah, Nahrawi (2025)
Soil carbon sequestration is a critical strategy for enhancing soil health and reducing the impact of climate change. The potential of bamboo to facilitate soil carbon storage and ecosystem restoration has garnered significant attention due to its high renewable potential and rapid growth (Kotangale et al., 2025). Due to its extraordinary capacity to enhance below-ground carbon sequestration through substantial root biomass, soil organic matter accumulation, and microbial interactions, bamboo is a viable alternative for sustainable soil management (Nath et al., 2015; Shoudho et al., 2024). As bamboo plantations have also been recognised for their ability to restore degraded land, they are an exceptional alternative to sustainable land-use planning.